A theoretical and experimental investigation on flow boiling of organic refrigerants at high reduced temperatures - Marchetto, Daniel Borba (2025)
New technologies have been developed to mitigate the use of non-renewable sources of energy and reuse the heat inherently wasted from a diverse range of processes. Among the variety of power cycles that have been proposed for this purpose, the Organic Rankine Cycle (ORC) is one of the promising alternatives. Although the number of publications involving ORCs has rapidly grown in recent years, flow boiling experimental studies in the operational range of these systems is still scarce. The shortage of experimental studies is even more pronounced considering investigations in small diameter channels and using low-global warming potential refrigerants (GWP). In this context, the present doctoral thesis involves the experimental and theoretical study on flow boiling of organic refrigerants at saturation temperatures (Tsat) of 50130°C inside horizontal channels with diameters of 1.22 and 2.07 mm. The experimental campaign yielded over 1300 results for pressure drop and heat transfer coefficient (HTC), with the corresponding flow patterns recorded, during flow boiling of R245fa and its low-GWP substitute candidates, R1233zd(E) and R1336mzz(Z). The experimental data was parametrically analyzed, revealing that the frictional pressure gradient increased with increasing mass velocity and reducing saturation temperature and channel diameter. The heat transfer coefficient experimental results indicated the superposition of convective and nucleate boiling effects, with their relative contributions varying according to the experimental condition. Increasing heat flux and saturation temperature increased the HTC, whereas mass velocity increments led to an increase in the heat transfer coefficient only at convective-dominated heat transfer conditions. Under similar saturation temperatures, the low-GWP refrigerants exhibited higher pressure drops and lower heat transfer coefficients, indicating that the drop-in replacement of R245fa by those fluids implies on a thermal hydraulic performance reduction. The experimental results were compared against an extensive list of prediction methods from literature. Reasonable accurate predictions of the frictional pressure gradient were achieved regardless of the saturation temperature, whereas the majority of the HTC prediction methods showed a progressive loss of accuracy with increasing Tsat . Moreover, the comparisons revealed that, in general, the prediction methods fail to accurately capture the HTC trends against vapor quality observed in the experimental data. These findings motivated the development of a new analytical-empirical model, based on the heat flux partitioning approach and liquid film thickness, to predict the flow boiling heat transfer coefficient during annular flow in small diameter channels. This model predicted 86.0% of the experimental data within error bands of ±30%, achieving a mean absolute error of 18.2%.